Elaboration and application of the didactic guide: “Tasks on HOTS” built on Task based learning and High Order Thinking skills, to develop the Speaking skill on students of 4th English level at the Language Center, Health and Sciences Faculty, National University of Chimborazo, period 2015. - Fuertes López, Blanca Narcisa (2016)
The research work “Elaboration and application of the didactic guide: Tasks on HOTS (High Order Thinking Skills) built on Task based learning and High Order Thinking skills, to develop the Speaking skill on students of 4th English level at the Language Center, Health and Sciences Faculty, National University of Chimborazo, period 2015”; aims three objectives: first, to apply the didactic guide “Tasks on HOTS” to develop the Spoken language; second, to assess the use of HOTS (High Order Thinking Skills) to enhance the speaking skill; and third, to evaluate the qualitative aspects of oral interaction and oral production. All of them with the purpose to overcome the poor spoken language performance of students. The research design type was quasi-experimental, at a descriptive level. It is a transversal and experimental study, which has been developed as a field, applied research. It was conducted with the scientific, and induction research methods using three techniques: survey, observation and test. The sample was purposive sampling which took 40 students, 20 of 4th level “A” (experimental group), and 20 of 4th level “E” (control group). After the analysis and interpretation of results, the statistical techniques student t-test and chi-square test were used for hypothesis testing. This research work implemented the didactic guide “Tasks on HOTS” which proposed a pedagogical intervention based on interaction between Task based learning and High thinking skills, assisting mainly learner´s needs to improve the spoken language by achieving learning outcomes within a real life-like context. “Tasks on HOTS” comprised 3 areas academic, vocational and recreational. The findings evidenced a high level of satisfaction and progress on 3 aspects: Application of the guide, development of Learners’ high order thinking skills and on Students’ Oral Interaction and Oral Production. Therefore, the study concluded accepting the main hypothesis stating that the Elaboration and application of the didactic guide: “Tasks on HOTS” built on Task based learning and High Order Thinking skills develops the Speaking skill because most students are able to achieve satisfactory standards on their ongoing and final oral performance on their speaking skill.